REFLEKSI TERHADAP PENJAJAHAN BANGSA BARAT DAN PERJUANGAN KEMERDEKAAN NEGARA-NEGARA ISLAM - Hutagaluh, Oskar; Syukur, Syamzan; Susmihara, Susmihara (Borneo : Journal of Islamic Studies, 2023)
This research sets out the problems faced by Muslims. So great was the struggle of Muslims in fighting for Islam, but this could not be achieved by Muslims because the three major Islamic empires experienced decline in various fields, such as politics, military, economics, science, and culture. This study aims to reflect on western colonization in Islamic countries and then explore the positive side. This study applies a qualitative method. The approach used is the historical approach. Based on this research, it was revealed that the decline that occurred in the Islamic world was caused by the Islamic kingdoms no longer having militant rulers and tough militaries, resulting in rebellions that were difficult to control. Meanwhile, the progress experienced by Western nations was due to developments made in the fields of science and civilization, which were previously neglected during the advancement of the three great Islamic empires, especially the Ottoman Empire. The value of reflection from this research is that Muslims will return to glory if they are able to master all lines, be they military, science, culture, economics, politics, or other strategic fields.